Electrical and structural adaptations of the paediatric athlete's heart: a systematic review with meta-analysis. Issue 4 (31st March 2017) - McClean, Gavin; Riding, Nathan R; Ardern, Clare L; Farooq, Abdulaziz; Pieles, Guido E; Watt, Victoria; Adamuz, Carmen; George, Keith P; Oxborough, David; Wilson, Mathew G
Abstract : Aim: To describe the electrocardiographic (ECG) and echocardiographic manifestations of the paediatric athlete's heart, and examine the impact of age, race and sex on cardiac remodelling responses to competitive sport. Design: Systematic review with meta-analysis. Data sources: Six electronic databases were searched to May 2016: MEDLINE, PubMed, EMBASE, Web of Science, CINAHL and SPORTDiscus. Inclusion criteria: (1) Male and/or female competitive athletes, (2) participants aged 6–18 years, (3) original research article published in English language. Results: Data from 14 278 athletes and 1668 non-athletes were included for qualitative (43 articles) and quantitative synthesis (40 articles). Paediatric athletes demonstrated a greater prevalence of training-related and training-unrelated ECG changes than non-athletes. Athletes ≥14 years were 15.8 times more likely to have inferolateral T-wave inversion than athletes <14 years. Paediatric black athletes had significantly more training-related and training-unrelated ECG changes than Caucasian athletes. Age was a positive predictor of left ventricular (LV) internal diameter during diastole, interventricular septum thickness during diastole, relative wall thickness and LV mass. When age was accounted for, these parameters remained significantly larger in athletes than non-athletes. Paediatric black athletes presented larger posterior wall thickness during diastole (PWTd) than Caucasian athletes. Paediatric male athletes also presented larger PWTd than females. Conclusions: The paediatric athlete's heart undergoes significant remodelling both before and during 'maturational years'. Paediatric athletes have a greater prevalence of training related and training-unrelated ECG changes than non-athletes, with age, race and sex mediating factors on cardiac electrical and LV structural remodelling.